2001
DOI: 10.4049/jimmunol.167.7.3585
|View full text |Cite
|
Sign up to set email alerts
|

A Pivotal Role of Rho GTPase in the Regulation of Morphology and Function of Dendritic Cells

Abstract: Dendritic cell (DC) is the most potent activator of CD4+ T cells and has unique dendrites and veils. To explore the function of Rho in DC, exoenzyme C3 from Clostridium botulinum was used as a specific inhibitor of Rho. Treatment of DC with C3 (DC/C3) resulted in profound morphological changes by losing dendrites and emerging of shrunk membrane processes that were in parallel with marked reduction of polymerized actin in the marginal area. Inactivation of Rho-associated coiled coil-containing kinase (p160ROCK)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 45 publications
(29 reference statements)
4
62
0
1
Order By: Relevance
“…In the same adhesion-based system, inhibition of p160ROCK, a downstream effector kinase of RhoA, led to the formation of longer dendrites due to a defect in cellular contraction and adhesion regulation (10). Conversely, treatment of monocytederived DCs with the Rho GTPase inhibitor exoenzyme C3 was found to induce the loss of the constitutive filamentous surface projections of DCs and to reduce the alloantigen-presenting capacity of these cells (11). However, exoenzyme C3 not only inhibits the GTPase Rho, but presumably also induces active depolymerization of F-actin by removing the cofilin-dependent brake for F-actin decay (12).…”
Section: Endritic Cells (Dcs)mentioning
confidence: 99%
See 1 more Smart Citation
“…In the same adhesion-based system, inhibition of p160ROCK, a downstream effector kinase of RhoA, led to the formation of longer dendrites due to a defect in cellular contraction and adhesion regulation (10). Conversely, treatment of monocytederived DCs with the Rho GTPase inhibitor exoenzyme C3 was found to induce the loss of the constitutive filamentous surface projections of DCs and to reduce the alloantigen-presenting capacity of these cells (11). However, exoenzyme C3 not only inhibits the GTPase Rho, but presumably also induces active depolymerization of F-actin by removing the cofilin-dependent brake for F-actin decay (12).…”
Section: Endritic Cells (Dcs)mentioning
confidence: 99%
“…Where indicated, postnuclear supernatants were incubated with 60 mM NOG for 20 min to destroy lipid rafts. In a different set of experiments, raft fractions (5-9) and soluble fractions (10,11) were pooled or kept separate. Fractions were briefly incubated at room temperature and subjected to PAK 1 precipitation described below.…”
Section: Pak 1-based Pull-down (Pd) Assays For Gtpase Activitymentioning
confidence: 99%
“…The Rho family encompasses three different subfamilies of small GTPases, all controlling the actin cytoskeleton: (i) Rho subfamily, which induces the assembly of F-actin stress fibers, typical of adhering cells; (ii) Rac subfamily, involved in the ruffling activity, typical of spreading cells; and (iii) Cdc42 subfamily, which is of relevance in the generation of the cell filopodia [10]. Interestingly, some lines of evidence have previously indicated that the impairment of this molecules results in the hindering of both extension and contraction of dendrites in mature DCs [11,12]. Furthermore, Rac-1 molecule activation seems to be required for short-range migration and T cell priming [13].…”
Section: Introductionmentioning
confidence: 99%
“…This step is followed by the accumulation of MHC and costimulatory molecules to the contact point between the T cell and the APC. Recent studies using specific inhibitors of F-actin polymerization, like cytochalasin D and botulinum toxin, have shown that the active reorganization of the cytoskeleton on the DC site is critically involved in T cell activation and proliferation (27,28). Interestingly, we found that UVBR of DC not only interferes with F-actin bundling but also leads to a massive Ca 2ϩ influx in ϳ10% of DC-T cell interactions.…”
Section: Discussionmentioning
confidence: 69%
“…Here, the bundling of F-actin with small Rho GTPases seems to be of critical importance, because inhibition of F-actin bundling directly interferes with the activation of naive, resting T cells (27,28). Therefore, we wished to determine whether UVBR interferes with F-actin bundling in DC.…”
Section: Uvbr Of DC Interferes With Early Activation Of Cd4mentioning
confidence: 99%